Hepatic iron quantification by atomic absorption spectrophotometry: Full validation of an analytical method using a fast sample preparation. Issue 3 (2007) - Wortmann Wortmann, A. C. A. C.; Froehlich Froehlich, P. E. P. E.; Pinto Pinto, R. B. R. B.; Magalhães Magalhães, R. B. R. B.; Álvares-da-Silva Álvares-da-Silva, M. R. M. R.; Ferreira Ferreira, J. J. J. J.; Silveira Silveira, T. R. T. R.
Abstract : Atomic absorption spectrophotometry is considered the method of choice for hepatic iron quantification. The objective of the present study was to perform full validation assays of hepatic iron quantification by atomic absorption spectrophotometry, using a fast sample preparation procedure, following the guidelines from the International Conference on Harmonization. The following parameters were evaluated: specificity, linearity/range, precision, accuracy, limit of detection and limit of quantification. A good linear correlation was found (0.9948) in the concentration range evaluated (20- 120 ppb). The relative standard deviations were below 15% for accuracy, and below 10% for both day-to-day reproducibility and within-days precision, and the repeatability of injections was 0.65%. Limit of detection was 2 ppb, and limit of quantification was 6 ppb. Fresh bovine liver tissue was used to evaluate the procedure of collecting samples by liver biopsies. These findings indicate that hepatic iron quantification by atomic absorption spectrophotometry can be reliably performed at the established conditions, and suggest the method is suitable for further use in clinical practice. Hepatic iron quantification by AAS is validated by the experiments performed in the present study.